Enhancing Success of Veterinary Visits for Clients With Disabilities and an Assistance Dog or Companion Animal: A Review - Grigg, Emma K.; Hart, Lynette A. (Frontiers in Veterinary Science, 2019)
Despite increasing information on enhancing client communication and compliance/adherence in veterinary medicine, literature focusing on special cases remains limited: working with clients with special needs, challenges or disabilities, or when the patient is an assistance or emotional support animal. This paper summarizes current recommendations on how best to build successful working relationships with these clients, including action items to implement in practice. In addition, this paper reviews current literature on important considerations for care of assistance dogs as patients.